2010
DOI: 10.1002/ijc.25187
|View full text |Cite
|
Sign up to set email alerts
|

α5β1 integrin antagonists reduce chemotherapy‐induced premature senescence and facilitate apoptosis in human glioblastoma cells

Abstract: The a5b1 integrin represent a new therapeutic target for glioblastoma, which are malignant brain tumors difficult to cure with conventional therapies. Glioblastoma are known to be highly resistant to chemotherapy. We, therefore, investigated whether blocking a5b1 integrin with specific nonpeptidic antagonists concomitantly with chemotherapy (ellipticine and temozolomide) may impact the response to chemotherapy of human glioblastoma. Here we show that inhibiting a5b1 integrin with 2 selective ligands (SJ749 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 45 publications
4
65
0
1
Order By: Relevance
“…Along with others, we demonstrated that p53-induced activation either by genotoxic drugs 24 or by inhibitors of HDM2 such as Nutlin-3a-triggered 25 senescence rather than apoptosis in GBM. We characterized a negative crosstalk between α5β1 integrin and p53wt implicated in temozolomide (TMZ) resistance.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Along with others, we demonstrated that p53-induced activation either by genotoxic drugs 24 or by inhibitors of HDM2 such as Nutlin-3a-triggered 25 senescence rather than apoptosis in GBM. We characterized a negative crosstalk between α5β1 integrin and p53wt implicated in temozolomide (TMZ) resistance.…”
supporting
confidence: 77%
“…We demonstrated that α5β1 integrin interferes with the p53 pathway and that Nutlin-3a (10 μM) represses the α5 integrin subunit through the activation of p53. 8,24 We wondered whether α5 integrin repression would sensitize glioma cells to Nutlin-3a. We treated U87MG cells overexpressing (U87MG-α5 high) or repressed (U87MG-α5 low) for α5 integrin with different doses of Nutlin-3a and evaluated their clonogenic potential.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the use of non-peptidic a5b1 integrin antagonists and GBM cell lines, we previously showed that a5b1 integrin may be a therapeutic target for these tumors (8,9) and that concomitant addition of a5b1 antagonists sensitizes p53 wild-type (p53-wt) glioma cells to chemotherapeutic drugs (10). The presence of p53 mutations in high-grade glioma varied across GBM subtypes with 0%, 21%, 32%, and 54% in classical, neural, mesenchymal, and proneural subtypes, respectively (11).…”
Section: Introductionmentioning
confidence: 99%
“…Several senescence-inducing pathways have been described, the principal being the P19Arf/P53 axis. As P53 has been involved in Temozolomide induction of senescence in U87 cells (28) and because our gene expression analysis showed over-expression of P53 and P53 targets (2), we addressed the involvement of P53 in the response of U87 cells to HQNBA derivatives. First, we found that over-expression of P53 and a set of several potential P53 targets specifically occurred exclusively in the presence of bio-active HQNBA derivatives but not when HQNBA analogs belonging to the same chemical series but lacking activity on cell proliferation and migration were used.…”
Section: Discussionmentioning
confidence: 99%